Analisis Efisiensi Penggunaan Faktor Produksi pada Usahatani Cengkeh di Desa Manggissari - Adyatma, I Wayan Chandra; Budiana, Dewa Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
In an agrarian country like Indonesia, agriculture has contributed greatly both to the economy and the fulfillment of basic needs of society. Agriculture is often underestimated by the upper middle class, farmers considered the dirty work and synonymous with poverty. The purpose of this study was to determine the effect of the use of factors of production land, seed, fertilizer, capital, and labor costs to total production of cloves in the Village District Manggisari Pekutatan and to determine the level of efficiency in farming activities in the Village Manggisari clove Pekutatan District. In this study the type of data used is a form of secondary data is data that has been collected by another party prior to or through a new data search. In this case such a data rate of production, land, seed use, fertilizer use, the amount of capital and labor in the farming cloves. The analysis used in this study includes two methods of analysis, namely multiple linear regression analysis and analysis efficiency. Linear Regression analysis is used to quantify the effect of more than one predictor variables (independent variables) on the dependent variable. The results showed variable land area (X1), seeds (X2), fertilizer (X3), the purchase of capital (X4), and total wage labor (X5) have a significant effect simultaneously and partially on the farm in the village of clove Manggisari Pekutatan District District Jembrana. Level of efficiency of the use of factors of production in the farming village of Manggisari cloves in Jembrana District Pekutatan simultaneously inefficient, two research variables, namely seeds (X2) and fertilizer (X3) its not efficient, while the other variables, namely land area (X1), purchase capital (X4), and total wage labor (X5) nature inefficient.
Keywords: Productivity; Land; Seed; Fertilizer; Capital; Labor Wages